Televisão: a presença do telespectador na configuração discursiva da interatividadenos programas de informação - a experiência do fantástico - Kieling, Alexandre Schirmer (Universidade do Vale do Rio do Sinos, 2009)
The materiality of the convergence of media due to digitalization processes of the production and content distribution means stands have configured new dynamics, both in the relationship between producers and receptors and in the texts which result from it. Our research study claims that these dynamics configure an ambience in which the logics of the open and closed systems operate interdependently and in which the space we define as „mediasphere‟ is constituted. This space is understood as a production, publication and consumer place in which the subjects of communication share texts and construct discourses, thus producing meanings which articulate symbolic goods. Despite being distinct from the real audience, this space proves to be able to configure realities and discursive worlds which are intrinsic to it and which, on the other hand, are characterized as a virtual public space, due to its dynamic and to the interactions it experiences. We verified our claim in the light of the interactive experien
Keywords: ambiência; gêneros; interação; interatividade; digitalização da TV; ambience; genre; interaction; interactivity; digitalization of TV; Ciências Sociais Aplicadas